2011
DOI: 10.1038/onc.2011.157
|View full text |Cite
|
Sign up to set email alerts
|

Uncommitted precursor cells might contribute to increased incidence of embryonal rhabdomyosarcoma in heterozygous Patched1-mutant mice

Abstract: Embryonal rhabdomyosarcoma (ERMS) is a tumor of the skeletal muscle in children and is frequently initiated by heterozygous germline mutations in the Hedgehog (Hh) receptor Patched1 (Ptch), both in humans and mice. Using a conditional knock-out strategy in Ptch flox/ þ mice, we demonstrate that early embryonic stages are more susceptible to ERMS development than later stages and that cells normally not committed to undergo myogenesis at this stage represent the major source of ERMS. We found that deletion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The molecular pathogenesis of the embryonal RMS is less clear, although allelic loss at chromosome 11p15, a locus overlapping with a Beckwith-Wiedemann syndrome critical region [8], was reported [9], and aberrant activation of the Sonic Hedgehog pathway was linked to the embryonal RMS in mice [10, 11]. Both forms of RMS are thought to be derived from myogenic progenitors as the consequence of impaired differentiation due to genetic lesions [12-14]. Current conventional treatments for RMS show varying prognostic outcomes, depending on the location of the tumor [1].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular pathogenesis of the embryonal RMS is less clear, although allelic loss at chromosome 11p15, a locus overlapping with a Beckwith-Wiedemann syndrome critical region [8], was reported [9], and aberrant activation of the Sonic Hedgehog pathway was linked to the embryonal RMS in mice [10, 11]. Both forms of RMS are thought to be derived from myogenic progenitors as the consequence of impaired differentiation due to genetic lesions [12-14]. Current conventional treatments for RMS show varying prognostic outcomes, depending on the location of the tumor [1].…”
Section: Introductionmentioning
confidence: 99%
“…Mice heterozygous for the Hh receptor Ptch develop embryonal subtype-like RMS [1214]. Therefore, these mice present a suitable model for the preclinical evaluation of Hh pathway antagonists in the treatment of ERMS, in which Hh signaling is active.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently suggested that p53 inactivation could lead to the induction of IGF2 and to the production of immature pluripotent stem cells [33]. Rhabdomyosarcoma could originate from such increased uncommitted precursors, as suggested by data on the Ptch rhabdomyosarcoma model [34], through the interaction with HER-2 expression. HER-2 is best known for its involvement in breast cancer, however it has major functions in muscle cells, for example it is required for the survival of human myoblasts [35], and is frequently expressed in human rhabdomyosarcoma [11].…”
Section: Discussionmentioning
confidence: 99%